Allergen-Specific Treg Cells Upregulated by Lung-Stage S. japonicum Infection Alleviates Allergic Airway Inflammation - Li, Zhidan; Zhang, Wei; Luo, Fang; Li, Jian; Yang, Wenbin; Zhu, Bingkuan; Wu, Qunfeng; Wang, Xiaoling; Sun, Chengsong; Xie, Yuxiang; Xu, Bin; Wang, Zhaojun; et al. (Frontiers in Cell and Developmental Biology, 2021)
Schistosome infection showed protective effects against allergic airway inflammation (AAI). However, controversial findings exist especially regarding the timing of helminth infection and the underlying mechanisms. Moreover, most previous studies focused on understanding the preventive effect of schistosome infection on asthma (infection before allergen sensitization), while the therapeutic effects of schistosome infection (allergen sensitization before infection) on asthma were rarely investigated. In this study, we investigated the therapeutic effects of schistosome infection on AAI using a mouse model of OVA induced asthma. To explore how the timing of schistosome infection influences its therapeutic effect, the mice were percutaneously infected with cercaria of Schistosoma japonicum at either 1 day (infection at lung-stage during AAI) or 14 days before OVA challenge (infection at post lung-stage during AAI). We found that lung-stage schistosome infection significantly ameliorated OVA-induced AAI, whereas post lung-stage infection didn’t. Mechanistically, lung-stage schistosome infection significantly upregulated the frequency of Treg, especially OVA specific Treg, in lung tissue, which negatively correlated with the level of OVA specific IgE. Depletion of Treg in vivo partially counteracted the therapeutic effect of lung-stage schistosome infection on asthma. Furthermore, transcriptomic analysis of lung tissue showed that lung-stage schistosome infection during AAI shaped the microenvironment to favor Treg induction. In conclusion, our data showed that lung-stage schistosome infection could relieve OVA induced asthma in a mouse model. The therapeutic effect was mediated by the upregulated OVA specific Treg which suppressed IgE production. Our results may facilitate the discovery of a new therapy for AAI.